Targeting ALK Rearrangements in NSCLC: Current State of the Art - Peng, Ling; Zhu, Liping; Sun, Yilan; Stebbing, Justin; Selvaggi, Giovanni; Zhang, Yongchang; Yu, Zhentao (Frontiers in Oncology, 2022)
Anaplastic lymphoma kinase (ALK) alterations in non-small cell lung cancer (NSCLC) can be effectively treated with a variety of ALK-targeted drugs. After the approval of the first-generation ALK inhibitor crizotinib which achieved better results in prolonging the progression free survival (PFS) compared with chemotherapy, a number of next-generation ALK inhibitors have been developed including ceritinib, alectinib, brigatinib, and ensartinib. Recently, a potent, third-generation ALK inhibitor, lorlatinib, has been approved by Food and Drug Administration (FDA) for the first-line treatment of ALK positive (ALK+) NSCLC. These drugs have manageable toxicity profiles. Responses to ALK inhibitors are however often not durable and acquired resistance can occur as on-target or off-target alterations. Studies are underway to explore the mechanisms of resistance and optimal treatment options beyond progression. Efforts have also been undertaken to develop further generations of ALK inhibitors. This review will summarize the current situation of targeting the ALK signaling pathway.